Late-Holocene oceanic variability in the southern Benguela region driven by interplay of upwelling, fluvial discharge, and Agulhas leakage. (February 2019) - Zhao, Xueqin; Dupont, Lydie; Schefuß, Enno; Granger, Robyn; Wefer, Gerold
The southern Benguela upwelling system near the St. Helena Bay has been proposed to be affected by various factors, while few investigations about the late-Holocene oceanic conditions has been carried out in this area. To determine the oceanic variability and its forcing mechanisms in the southern Benguela region during the late-Holocene, we examined organic-walled dinoflagellate cyst (dinocyst) records from two marine sediment cores located in the southernmost and central Benguela upwelling system. We compare our results with other proxies including alkenone-derived SSTs, grain size, and coccolithophore assemblages from the same samples. The results indicate a distinctive behavior between the southernmost Benguela system and the central Benguela area. We infer that the oceanic conditions in these two regions are primarily governed by an interplay of wind-induced upwelling, fluvial discharge, and advection of cold sub-Antarctic waters, which is consistent with the current understanding of the paleoclimate conditions in this area. However, the findings also suggest that the southernmost Benguela system also receives additional effects of warm and saline waters via the Agulhas leakage, which has a clear influence on the oceanic conditions in this area.